Labor market aspects of enclave-led growth - Ronald Winthrop Jones; Sugata Marjit (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
The parpose of this paper is to model and describe the consequences for labor markets in an underdeveloped economy of foreign Investment in an enclave sector.Foreign technology tends to expose some of the hidden talents in the local labor force.Replacement of foreign labor by domestic labor coupled with a process of skill revelation generate non monotonic wage and profit movements in the lQcal economy.We also discuss the effects of growth and skill development on the pattern of wage movement and the exit period of foreign personnel both in the fixed and variable proportions cases.
Keywords: 330; Arbeitsmarkttheorie; Sonderwirtschaftszone; Entwicklung; Theorie